Conventional and enhanced exergy analysis of a hydrogen liquefaction system. (6th January 2021) - Utlu, Zafer; Karabuga, Arif
Abstract: In the present work, conventional and enhanced exergy analyses were applied to the cryogenic liquefaction process of hydrogen gas. The hydrogen liquefaction unit consists of a multi-stage compressor, booster compressor-turbine pair, and heat exchanger block. Convectional exergy analysis cannot identify parts of exergy inefficiencies. In addition, by convectional exergy analysis, it cannot determine inevitable exergy losses that occur due to technological limits. For this reason, enhanced exergy analysis should be applied to the system. The exergy destruction affecting the exergy efficiency of the hydrogen liquefaction unit was investigated in detail. This study suggests an enhanced exergy analysis of a cryogenic liquefaction system. According to the results of the convectional exergy analysis, exergy efficiency of the whole liquefaction process are 32.22%. Also, the highest and lowest endogenous exergy destruction among whole components is calculated as 9563 kW and 92.83 kW in the turbine and CM-1, respectively. With these calculated results, the potential for improvement in the turbine in the liquefaction system was found to be high. Highlights: Enhanced exergy analysis of hydrogen liquefaction system was performed using cryogenic method. The overall exergy efficiency of the hydrogen liquefaction system is calculated as 32.22%. The total exergy destruction of whole components is calculated as 44, 915 kW. The lowest endogenous exergy destruction among whole components is calculated as 92.83 kW in the CM-1. The highest endogenous exergy destruction among whole components is calculated as 9563 kW in the turbine.